O cálculo dos benefícios previdenciários: uma análise qualitativa da proteção social - Rocha, José Francisco Furlan (2012)
The general social insurance system mainly relies on monetary mechanisms for coping with societal needs, elevating the theme "calculation and adjustment of benefits" to one of the main topics of study in the social security law. Through the analysis of criteria for determining the value and realignment of the benefits, the study aims to identify the main elements that influence the composition of the income as well as analyze the adequacy of the legal criteria of adjustment with the guarantees established by the Constitution of 1988. Using predominantly theoretical research, this study follows the deductive method, using also a comparative analysis to verify the compliance, by the legislator and public administration, of the constitutional guarantees related to the restatement of the contributions, benefit irreducibility and the maintenance of its real value